ORGANOLEPTIC VALUE OF BALI BEEF MARINATED WITH FRESH MORINGA LEAF, MORINGA LEAF TEA, AND MORINGA LEAF POWDER - I. G. N., ARDITE; SRIYANI, N. L. P.; SUARTA, G. (Majalah Ilmiah Peternakan; Vol 26 No 2 (2023): Vol. 26 No. 2 (2023)DO - 10.24843/MIP.2023.v26.i02.p07, 2024)
Bali beef is a meat that is quite attractive to the public. This study aims to find out the best ingredients and deter- mine the organoleptic value of Bali beef marinated using fresh moringa leaves, moringa leaf tea, and moringa leaf powder. Marinate the meat for 1 hour at room temperature. The research design used was a completely randomized design with four treatments and four replications. The four treatments were meat marinated with aquadest (P0); meat marinated using fresh moringa leaves 0.4% (P1); meat marinated using moringa leaf tea 0.4% (P2); and meat marinated using moringa leaf powder 0.4% (P3). The variables observed in this study were organoleptic tests of color, aroma, taste, texture, tenderness, and overall acceptance which were assessed by 15 semi-trained panelists. The results showed that Bali beef marinated using fresh moringa leaves, moringa leaf tea, and moringa leaf pow- der had a significant effect (P<0.05) on aroma, tenderness, and overall acceptance, but had no significant effect (P>0.05) on color, taste, and texture. The results of this study can be concluded that the best Bali beef marinade is using moringa leaf powder filtrate as much as 0.4% seen from the increase in the value of aroma, tenderness, and overall acceptance of the panelists.